2017
DOI: 10.4236/jtr.2017.54022
|View full text |Cite
|
Sign up to set email alerts
|

Drug Susceptibility Patterns of Mycobacterium tuberculosis Isolates from Tuberculosis Patients in Coastal Kenya

Abstract: Background: Tuberculosis (TB) is an infectious disease caused by the bacillus Mycobacterium tuberculosis. Anti-tuberculosis drug resistance is an emerging health problem in Kenya and especially in Coastal region. This is a major challenge in tuberculosis control. Diagnosis is based on Ziel-Neelsen staining alone and patients are treated without information on sensitivity patterns.Aim: This study aimed to determine drug susceptibility patterns of Mycobacterium tuberculosis in Coastal Kenya. Study Design: Hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
3
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 21 publications
(14 reference statements)
4
3
2
1
Order By: Relevance
“…The overall proportion of MDR-TB observed in our study was higher compared to previous studies conducted in Addis Ababa, Ethiopia [ 22 , 23 ], northwest Ethiopia [ 24 , 25 ], Jigjiga in the Somali Region [ 9 ] and the Oromia Region [ 26 ], which showed an overall prevalence of MDR-TB of 11.5%, 5.6%, 10.2%, 1.8%, 1.8% and 4.7%, respectively. The finding was also higher than the study done in China [ 27 ], Kenya [ 28 ], Tanzania [ 29 ], India [ 30 ], Vietnam [ 31 ], Lima Peru [ 32 ], Dalian China [ 33 ] and northeastern China [ 34 ], where the overall MDR-TB prevalence was estimated at 11.3%, 4.8%, 6.3%, 5.6%, 6.9%, 6.6%, 10.1%, 8.7%, respectively. Conversely, the overall MDR-TB proportion observed in our study was lower than former study findings, which showed a 39.4%, 27.2%, 39.2% and 26% overall MDR-TB prevalence reported from Addis Ababa, Ethiopia [ 12 ], southwest Ethiopia [ 10 ], Uganda [ 35 ] and Taiwan [ 36 ], respectively.…”
Section: Discussioncontrasting
confidence: 68%
“…The overall proportion of MDR-TB observed in our study was higher compared to previous studies conducted in Addis Ababa, Ethiopia [ 22 , 23 ], northwest Ethiopia [ 24 , 25 ], Jigjiga in the Somali Region [ 9 ] and the Oromia Region [ 26 ], which showed an overall prevalence of MDR-TB of 11.5%, 5.6%, 10.2%, 1.8%, 1.8% and 4.7%, respectively. The finding was also higher than the study done in China [ 27 ], Kenya [ 28 ], Tanzania [ 29 ], India [ 30 ], Vietnam [ 31 ], Lima Peru [ 32 ], Dalian China [ 33 ] and northeastern China [ 34 ], where the overall MDR-TB prevalence was estimated at 11.3%, 4.8%, 6.3%, 5.6%, 6.9%, 6.6%, 10.1%, 8.7%, respectively. Conversely, the overall MDR-TB proportion observed in our study was lower than former study findings, which showed a 39.4%, 27.2%, 39.2% and 26% overall MDR-TB prevalence reported from Addis Ababa, Ethiopia [ 12 ], southwest Ethiopia [ 10 ], Uganda [ 35 ] and Taiwan [ 36 ], respectively.…”
Section: Discussioncontrasting
confidence: 68%
“…The rate of MDR-TB identified in this study was 5.8%, (9/156) among new presumptive TB cases and this was congruent to the rate of MDR-TB reported in the previous studies by Tessema B et al, (3.7%, 2012) [28], Yigzaw WB et al, (5.0%, 2021) [40] in Ethiopia; Yonge SA et al, (4.8%, 2017) [46] in Kenya and Dosso M et al, (5.3%, 1999) [32] in CĂ´te d'Ivoire. However, compared to our study findings, a higher rate of MDR-TB was reported in the previous studies by Welekidan LN et al, (11.6%, 2020) [49], and Dagne B et al, (61.9%, 2021) [39] in Ethiopia; Ullah I et al, (9.3%, 2016) [35] in Pakistan; Monde N et al, (9.8%, 2023) [41] in Zambia, Thapa G et al, (15.6%, 2016) [42] in Nepal, Li Y et al, (13.2%, 2016) [43], and Zhou L et al, (18.8%, 2022) [50] in China and Aung WW et al, (18.3%,2015) [51], and Lobie TA et al, (2.3%, 2020) [30] in Ethiopia; Glasauer S et al, (3.3%, 2019) [34] in Germany.…”
Section: Discussionsupporting
confidence: 91%
“…Ndung'u PW et al, (30.0%, 2012) [44], Kerubo G et al, (30.0%, 2016) [45] and Yonge SA et al, (48.6%, 2017) [46] in Kenya; and Aung WW et al, (27.7%, 2015) [47] in Myanmar. However, a lower rate of resistance of M. tuberculosis strains in new presumptive pulmonary TB cases was reported in the previous studies by Biadglegne F et al, (6.7%, 2014) [48] in Ethiopia.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the average age of TB patients was 44.7 years, which is similar to the mean age of 41.2 years reported by Bilagi et al [11]. However, some earlier Nigerian studies reported lower mean age ranges [12,13]. The age groups that had the highest incidence of TB in this study were individuals aged 31-40 and 51-60 years old.…”
Section: Discussionsupporting
confidence: 85%